2016
DOI: 10.1111/gcbb.12346
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Sida (Sida hermaphrodita) biomass for multiple energy purposes

Abstract: The performance and biomass yield of the perennial energy plant Sida hermaphrodita (hereafter referred to as Sida) as a feedstock for biogas and solid fuel was evaluated throughout one entire growing period at agricultural field conditions. A Sida plant development code was established to allow comparison of the plant growth stages and biomass composition. Four scenarios were evaluated to determine the use of Sida biomass with regard to plant development and harvest time: (i) one harvest for solid fuel only; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 27 publications
4
70
2
Order By: Relevance
“…Because no fertilizers were used for Sida cultivation, low nitrogen concentration in harvested biomass could be attributed to nitrogen limitation in soil . Jablonowski et al (2016) showed that the first cut of Sida in June at a development stage of BBCH-Sida 55 displayed a TS content of 20%, while in our study it was 37.43%. However, silaging contributes to increasing VS and TS contents over time.…”
Section: Characteristics Of Feedstock Used For Anaerobic Digestioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Because no fertilizers were used for Sida cultivation, low nitrogen concentration in harvested biomass could be attributed to nitrogen limitation in soil . Jablonowski et al (2016) showed that the first cut of Sida in June at a development stage of BBCH-Sida 55 displayed a TS content of 20%, while in our study it was 37.43%. However, silaging contributes to increasing VS and TS contents over time.…”
Section: Characteristics Of Feedstock Used For Anaerobic Digestioncontrasting
confidence: 49%
“…It was similar to our results of biogas and methane production of 381.39 and 166.61 mL/g VS, respectively. Jablonowski et al (2016) achieved a biogas yield of 419.5 L/kg VS with methane concentration of 53.5% from the silage of Sida at the development stage of BBCH-Sida 55. In turn, the yield of methane production from the microalgae biomass may reach 240-307 mL/g VS for Chlorella vulgaris and 210-261 mL/g VS for Scenedesmus sp.…”
Section: Biogas/methane Production Rate and Yield From The Substratesmentioning
confidence: 99%
“…When used as solid fuel, parameters often determined are the higher heating value (HHV) and the lower heating value (LHV). In ten studies considered in this review, the HHV of Sida ranked between 16.5 and 19.5 MJ kg −1 dry matter (dm in the following) at an average of 18.4 ± 0.9 MJ kg −1 dm; the LHV between 14.0 and 17.2 MJ kg −1 dm at an average of 16.1 ± 1.2 MJ kg −1 dm (Borkowska et al ., , ; Wróblewska et al ., ; Smoliński et al ., ; Szyszlak‐Barglowicz et al ., ; Stolarski et al ., , ; Franzaring et al ., ; Tworkowski et al ., ; Siaudinis et al ., ; Jablonowski et al ., ). Whilst the HHV of Sida biomass appeared to be rather constant from November until April in one study, the LHV increased from 9.7 to 15.0 MJ kg −1 within this time span (Stolarski et al ., ), presumably owing to the changing water content of the biomass.…”
Section: The Use Of Sida As Biofuel: Biophysical and Biochemical Propmentioning
confidence: 97%
“…It even reached 88.1 % in another study, in which, however, the time of harvest was not given (Michalska et al ., ). In accordance with these findings, the contents of cellulose and lignin in the stems remained rather stable from June until December, whilst they increased during that time in the leaves (Jablonowski et al ., ).…”
Section: The Use Of Sida As Biofuel: Biophysical and Biochemical Propmentioning
confidence: 97%
“…The results were used to calculate the lower calorific value (LCV) using Eq. 1 (Brlek et al 2012;Jablonowski et al 2016…”
Section: Analysis Of Thermophysical Parametersmentioning
confidence: 99%